Economic sustainability of local food producers: a mixed methods study - Helgheim, Berit Irene; van der Linden, Natasha; Teryokhin, Sergei (Frontiers in Sustainable Food Systems, 2024)
This study investigates local food producers' economic sustainability by examining the impact of six variables: external and internal barriers, the number of economic operators, the imbalance of power, the number of distribution options, and waste. The investigation uses mixed methods of questionnaires and interviews. The data was collected using a self-completed questionnaire, which was answered by 57 local food producers across Norway, and four semi-structured interviews with professionals in the food industry. The quantitative data was analyzed with the use of partial least squares structural equation modeling (PLS-SEM), and the qualitative data was analyzed using a thematic analysis. The study has statistically confirmed three out of eight hypotheses. The three hypotheses show that when the number of economic operators in the supply chain increases and also imbalances in the sales channels increase. Additionally, the imbalance of power in the sales channels has a negative effect on economic sustainability, and external barriers have a negative effect on the imbalance of power in the sales channels. The interviews supported seven of the hypotheses, although four of them were not supported.